[3+2] Anionic Cycloaddition of Isocyanides to Acyclic Enamines and Enaminones: A New, Simple, and Convenient Method for the Synthesis of 2, 4‐Disubstituted Pyrroles. Issue 9 (19th February 2020) - Efimov, Ilya V.; Matveeva, Maria D.; Luque, Rafael; Bakulev, Vasiliy A.; Voskressensky, Leonid G.
Abstract : We herein demonstrate a new approach for the synthesis of 2, 4‐disubstituted pyrroles by [3+2] cycloaddition reaction of isocyanides to the activated double bond of various enamines and enaminones. This process paved the way for the synthesis a series of 2, 4‐disubstituted pyrroles, which are known to be intermediates in the synthesis of biologically active compounds, in good to excellent yields from simple and commercially available starting materials. The process is carried out efficiently using a strong base, t BuOK, at low temperatures (0 °C). The described method is simple, proceeds in one step, does not require additional catalysts and hence, has a wide scope. Abstract : Herein, a new route toward 2, 4‐substituted pyrroles is presented. This is a new, simple, fast, and convenient method furnishing 2, 4‐substituted pyrroles based on the formal cycloaddition reaction of isocyanides with acyclic enamines or enaminones under basic conditions.